2019
DOI: 10.3390/en12081425
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Large Scale PV-Based Generation into Power Systems: A Survey

Abstract: This paper reports a general overview of current research on analysis and control of the power grid with grid scale PV-based power generations as well as of various consequences of grid scale integration of PV generation units into the power systems. Moreover, the history of PV renewable growth, deregulation of power system and issues related to grid-connected PV systems considering its contribution to various responsibilities like frequency control, virtual inertia capabilities and voltage regulation are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 106 publications
(157 reference statements)
0
62
0
1
Order By: Relevance
“…Series compensation is provided by Static Synchronous Series Compensator (SSSC) and Thyristor-Controlled Series Capacitor (TCSC). [19][20][21] The STATCOM and SVC are examples of shunt compensation devices. The FACTS controller offers to regulate the transmission of AC, increasing or decreasing power flow in specific branch and response to stability issues.…”
Section: Power System Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Series compensation is provided by Static Synchronous Series Compensator (SSSC) and Thyristor-Controlled Series Capacitor (TCSC). [19][20][21] The STATCOM and SVC are examples of shunt compensation devices. The FACTS controller offers to regulate the transmission of AC, increasing or decreasing power flow in specific branch and response to stability issues.…”
Section: Power System Stabilitymentioning
confidence: 99%
“…The reactance of the lines is controlled by series connected FACTS devices while the shunt connected devices are used for compensation in transmission lines. Series compensation is provided by Static Synchronous Series Compensator (SSSC) and Thyristor‐Controlled Series Capacitor (TCSC) . The STATCOM and SVC are examples of shunt compensation devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the field of energy has shown that the penetration rate of photovoltaic (PV) power generation is expected to increase steadily over the next decade [1]. The existing small-scale PV systems dominating local demand has been replaced with bulk farm systems to take advantage of environmentally friendly policies as described in [2].…”
Section: Introductionmentioning
confidence: 99%
“…Solar power still has huge potential and the rate of installation has been growing drastically. A report by the European Photovoltaic Industry Association (EPIA) revealed that the European cumulative photovoltaic (PV) capacity, had increase to more than 120 GW from around 29 GW in 2010 [1]. The report suggests that the PV installation rates will continue to grow through the next decade.…”
Section: Introductionmentioning
confidence: 99%